STRUCTURAL OPTIMIZATION OF THE SYSTEM OF OPTICAL-ELECTRONIC OBSERVATION - Rachok, R. V.; Borovik, O. V.; Borovik, L. V. (Radio Electronics, Computer Science, Control, 2018)
Context. In border security uses a system of optical-electronic observation, which presents a set of towers that have radar, thermal imaging and video surveillance. The efficiency of detecting trespassers with the use of this system significantly depends on its functional and structural construction. The functional structure of system of optical-electronic observation is determined by the selection of technical means of surveillance (TCS) based on their functionality. Structure of the system depends on the choice of the locations of observation towers with the physical and geographical conditions of the terrain and technical characteristics of the TCS. The imperfection of the scientific methodological apparatus in the field of structural optimization of building of system of optical-electronic observation was determined by the relevance of the study. Objective. The aim of this work is to develop a method of structural optimization of the placement of the system of optical-electronic observation towers. Method. In work the task of optimizing the placement of the towers of system of optical-electronic observation and the proposed method of its solution, which involves the maximization of efficiency of functioning of the system. The peculiarity of this method is the use of geomodel to reduce the number of accommodation of the towers of the system, the use of the author’s approach to sampling of spatial data and high-speed algorithm for calculation of efficiency of functioning of system of optical-electronic observation. Results. The paper shows the advantages of the proposed method compared to previously proposed approaches for the choice of rational placement of towers on the basis of cluster analysis. In this work the proposed software-algorithmic implementation of the method to structural optimization of the system of optical-electronic observation. The authors describe the description of algorithmic and software implementation of this method. Using the developed software optimized placement of the towers of the system of optical-electronic observation, certain recommendations regarding the structure of this system. Conclusions. Using the proposed method allows to carry out structural optimization of building of system of optical-electronic observation due to the placement of observation towers with the maximization of efficiency of functioning of this system. A possible direction of improvement of the method is a refinement of the results using a higher resolution geomodel.